(untitled) (Journal of Student Research, 2015)
The purpose of this paper is to study the relationship between organizational incentives and employee discretionary effort. To examine this relationship data collected from 753 individual employees from 2003-2004 composing the Professional Worker Career Experience Survey, (PWCES) United States, was analyzed through a linear regression test. Results indicate a significant positive relationship between organizational incentives and employee discretionary effort. When organizational incentives increase, so does employee discretionary effort. The results of this study suggest that as businesses increase employee incentives, employee proactivity and satisfaction will increase. An increase in employee satisfaction results in increased employee productivity and company profitability. Possible limitations and future research on the measurement and study of discretionary effort are reviewed.